THE EFFECT OF ONLINE VIDEO BLOG ON STUDENTS’ ACHIEVEMENT OF PASSIVE VOICE IN 4J OPERATION KENDARI - Setiawan, Raden Alifian; Hanna, Hanna; Alberth, Alberth (Journal of Teaching of English, 2020)
The use of videos in education makes it possible to overcome practical real-world constraints and explore far greater possibilities provided by digital spaces, especially for the video uploaded in online platform such as blog. This study examines whether online video blog as media have a significant effect on students’ achievement of passive voice. It used pre-experimental (one group pre-test and post-test) design. The samples of this study were 10 students at 4J Operation. A pre-test and post-test were conducted by using multiple choice questions as the instruments. Data analysis was through paired-sample t-test. Results showed that there was an increase in mean score of pre-test (49,1) and post-test (63,5). Data from Paired Sample t-test showed that Sig. (2-tailed) was 0.000 which was smaller than .05 which means that there was significance difference in mean score after employing treatment.